RESPON SISWA TERHADAP PEMBELAJARAN MENGGUNAKAN MODEL SIKLUS BELAJAR 5E BERBANTUAN MULTIMEDIA PADA MATERI KOLOID - Sartika, Rody Putra (Universitas Tanjungpura, 2014)
This research aims to know students’ response about learning process using learning cycle 5E model assisted with multimedia on colloid matter. Pre-experiment method with one-shot case study design was used regarding to this. There are 79 students of SMAN 7 Pontianak who involved in this research. indirect communication techniques was used to collect data. Based on the research is obtained very good student response to learning using the 5E learning cycle model of multimedia-assisted colloid matter. The information that is obtained from this research is a very good response of students to learning using the 5E learning cycle model of multimedia-assisted colloid matter. Keywords: learning cycle 5E model, multimedia, students’ response, colloid. Abstrak: Penelitian ini bertujuan mengetahui respon siswa terhadap pembelajaran menggunakan model siklus belajar 5E berbantuan multimedia pada materi koloid. Untuk menjawab permasalahan digunakan metode pra-eksperimen dengan desain one-shot case study. Sebanyak 79 siswa SMAN 7 Pontianak terlibat dalam penelitian ini. Teknik pengumpulan data menggunakan komunikasi tak langsung.Berdasarkan hasil penelitian diperoleh informasi bahwa respon siswasangat baik terhadap pembelajaran menggunakan model siklus belajar 5E berbantuan multimedia pada materi koloid. Kata-kata kunci:Model siklus belajar 5E, multimedia, respon siswa, koloid.